Perception of Knowledge of the Risk of the COVID -19 Pandemic Regarding Touring Intentions and Tourism Travel Recommendations - RUDYANTO, Rudyanto; PRAMONO, Rudy; JULIANA, Juliana (Journal of Environmental Management and Tourism, 2021)
Tourists consider the costs, energy, and safety of the COVID-19 pandemic that is currently hitting the world globally. Tourism travel is expected to remain the primary choice for economic recovery and improving family relations. This study uses Respondent-Driven Sampling and Snowball Sampling to collect 432 respondents via social media and the internet. This study used a structural equation model (SEM) to examine risk perceptions of risk-averse attitudes by mediating knowledge of pandemic risk, tourism travel, and travel intentions. The results showed that most of the prospective tourists showed a preference for tourism. Tourists pay attention to the dangers of performance, costs, time, tourism destinations, while the social-psychological risks posed by the COVID-19 pandemic have a low impact. The nature and behaviour of tourists to avoid pandemic risk cause pandemic risk to be less effective in reducing tourists' intention to travel. Understanding pandemic risk effectively reduces risk perceptions that potential tourists have on tourism travel. The purpose of travelling and the intent to recommend tourism travel harms risk avoidance attitudes higher than the risk perception of a pandemic. All tourism travel stakeholders must consider the mediating effect of risk perception and risk aversion attitudes in tourism.